COMPARISON OF THE LENGTH OF STAY OF COVID-19 PATIENTS WITH COMORBID DIABETES MELLITUS BY GENDER AT NATAR MEDIKA HOSPITAL SOUTH LAMPUNG IN 2021 - Firhat, Esfandiari; Dhyta, Kinantie Lintang; Tusy , Triwahyuni; Fransisca, Sinaga (Transpublika Publisher, 2022)
Based on existing data, comorbid hypertension and diabetes mellitus, male gender, and active smoking are risk factors for SARS-CoV-2 infection. Diabetes mellitus (DM) is a metabolic disorder that affects insulin action in glucose absorption. A study conducted by Parveen et al showed that diabetes made the general health condition of COVID-19 patients worse. COVID-19 patients require hospitalization because COVID-19 is a highly contagious respiratory infectious disease, which can cause respiratory, physical, and psychological dysfunction of the patient, also resulting in various dysfunctions, which in turn can reduce the patient's functional capacity. This study aims to determine the difference in length of stay for COVID-19 patients with comorbid diabetes mellitus based on gender at Natar Medika Hospital, South Lampung in 2021. This type of research uses a comparative descriptive research method. The research design used in this study was cross sectional. Samples that met the inclusion and exclusion criteria were 40 patients' medical records. Gender characteristics were dominated by 24 women (60%) and 16 men (40%). A total of 14 female patients (58.3%) and 12 male patients (75%) recovered quickly. While 4 male patients (25%) and 10 female patients (41.7%) recovered for a long time. It is known that there is no significant comparison of length of stay for COVID-19 patients with comorbid diabetes mellitus based on gender where the Mann-Whitney test obtained a significance level (ρ value) of 0,466.